Survival of the Sawfly Athalia rosae Upon Infection by an Entomopathogenic Fungus and in Relation to Clerodanoid Uptake - Zanchi, Caroline; Lo, Lai Ka; R, Reshma; Moritz, Isabel; Kurtz, Joachim; Müller, Caroline (Frontiers in Physiology, 2021)
Larvae of the cabbage leaf sawfly Athalia rosae are a pest of Brassicacae plants, as their feeding can cause defoliation of various crops of economic importance. The larvae and the adults of this sawfly species are known to take up different classes of chemical compounds from their respective host plants, with potentially deterrent functions against predators. In addition, compounds taken up by the adults, the clerodanoids, are known for their antimicrobial activity. These features could be a challenge to biocontrol strategies. Several natural enemies of A. rosae have been identified, targeting larval and pupal stages of A. rosae, which could potentially be used as biocontrol agents. However, targeting the adult stage of a larval pest in addition to targetting the juvenile stages may improve population control. In this study, we ask whether a strain of the entomopathogenic fungus Beauveria bassiana shows biological activity against A. rosae adults. We also investigate whether the behavior of clerodanoid uptake by the adults, which is commonly found, affects their survival in response to a B. bassiana exposure. We found a clear dose-response relationship, i.e., with increasing fungal conidia concentrations survival of A. rosae decreased. However, there was only a low incidence of mycelial growth and sporulation from A. rosae cadavers, indicating that either the fungus is not successfully developing inside this host, or it is not able to re-emerge from it. Clerodanoid uptake decreased the survival of healthy adults, however, it did not increase their survival to B. bassiana. Our results revealed that this strain of B. bassiana if applied alone is probably not suitable for biocontrol of this sawfly species, because A. rosae showed a high baseline resistance against this fungus. The behavior of clerodanoid uptake is unlikely to have evolved as a defense against this entomopathogenic fungus.